Investigating sports and disaster relief management within the framework of social integration: The case of Kahramanmaraş earthquake - Türkay Hikmet; Genç Ayça; Yiğit Şıhmehmet; Üstün Ümit Doğan; Tugal Aygül; Dere Gamze (EDP Sciences, 2024)
Efficient disaster management and crisis response frequently depend on the integration of society and the involvement of community organizations. Specifically, prominent sports organizations, sports managers, and athletes have a crucial responsibility in offering disaster relief and support to individuals impacted by disasters. The purpose of this study is to examine the disaster relief efforts and initiatives provided by various institutions and individuals after the Kahramanmaraş earthquake, as well as to provide an overview of a project conducted by the authors. The present study conducted a comprehensive analysis of 86 newspapers and television news reports that focused on disaster relief efforts carried out by different sports organizations, sports managers, and athletes in various regions of Turkey. The data was analyzed using content analysis methods. This research analyzed documentary and visual records pertaining to the earthquake disaster that occurred in Kahramanmaraş on February 6, 2023, as part of the data collection process. Data analysis identified a range of sports activities carried out by sports organizations, sports managers, and athletes to provide social support in the disaster-stricken area. These activities manifest in both tangible and emotional forms, highlighting the significance of sports in fostering social integration. As a conclusion we believe the current study revealing the prevalence and uniqueness of postdisaster relief activities by sports organizations, sports managers, and athletes might be a precedent for future research.
Keywords: H; Social Sciences